STUDYING IMMUNOBIOLOGICAL FEATURES OF PREPARED WATER_SALT EXTRACTS OF INSECT ALLERGENS - O.V. Radikova; I.S. Kropotova; S.V. Khlgatyan; N.S. Petrova; V.M. Berzhets (Union of pediatricians of Russia, 2008)
Through the indirect degranulation of mast cells, anaphylaxis test, solid phase immune enzyme analysis, the researchers evaluated the immuno biological features of serum of 20 patients suffering from atopic mild and moderate bronchial asthma with domestic sensitization. All received water salt extracts of insects (cockroach, black beetle, American cock roach, ash gray cockroach, cricket, fly, moth, mealworm, weevil, billbug) demonstrated specific activity. An immune enzyme analysis has revealed more intensive allergic features of substances extracted from black beetle, cockroach, fly and moth.Key words: insect allergens, allergen specific immunotherapy, immuno biological features of allergic extracts, Ige anti bodies.